Eksistensi Birokrasi di Era Revolusi 4.0: Penggunaan Electronic Government dalam Optimalisasi Pelayanan: The Existence of Bureaucracy in the Revolutionary Era 4.0: The Use of Electronic Government in Service Optimization - Muhammad Reza Fahlevy; Muhammad Hairul Saleh; Niken Nurmiyati (JOURNAL OF GOVERNMENT SCIENCE, 2023)
This study aims to determine the existence of bureaucracy in the era of the industrial revolution 4.0. This study used the descriptive qualitative method. The results of the study show that the industrial revolution 4.0 brought significant changes to the conditions of the bureaucracy in Indonesia. This is supported by data that Indonesia is ranked 5th in Southeast Asia with an electronic-based government system or known as e-government. E-government services in the Industry 4.0 era are very important for the government because the presence of e-government makes the service process carried out by the government have good accountability and transparency, this certainly affects the number or complexity of services in the bureaucracy. With the existence of e-government, it will improve the quality of public services from those that initially had pathology to now an innovative bureaucracy.